Combined phase-field crystal plasticity simulation of P- and N-type rafting in Co-based superalloys. (15th August 2019) - Wang, Chan; Ali, Muhammad Adil; Gao, Siwen; Goerler, Johannes V.; Steinbach, Ingo
Abstract: We combine a phase-field model with a crystal plasticity model to simulate the microstructural evolution during creep in the Co-based superalloy ERBOCo-2Ta. Three-dimensional simulations of tensile and compressive creep tests in [100] direction were performed to study the rafting behavior in Co-based superalloys. The loss of coherency between γ matrix and γ′ precipitate, which is essential for the understanding of rafted structures, is modeled in relation to the dislocation activity in the γ-channels. Special attention is given to the interplay between creep deformation and microstructure stability. Appropriate constitutive modeling is applied to simulate realistic microstructure evolution under creep conditions. Thus, with the removal of the misfit stress, γ′ precipitates lose their cuboidal shape and form rafts. During N-type rafting more γ′ precipitates coalesce than during P-type rafting. The γ′ volume fraction during rafting increases under tensile stress but decreases under compressive stress. The morphological evolution of γ′ precipitates under tensile and compressive stresses in Co-based superalloy is consistent with the rafting characteristics in experimental observations. Graphical abstract: Image 1